Iowa Birdline update, December 10, 1990, notes - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Notes for the Iowa Birdline update for December 10, 1990. Highlights of the notes include the continued presence of a Yellow Grosbeak and sightings of Black-legged Kittiwakes and Bohemian Waxwings. Other interesting observations were a Northern Saw-whet Owl, Loggerhead Shrikes, and RInged Turtle-Doves. Epson - sheet feed/flatbed